Employing West Life to Improve EFL Pronunciation in Blended Learning Environment - Nazara, Situjuh (JET (Journal of English Teaching), 2017)
In EFL classrooms, pronunciation has often been the most neglected teaching-learning component. As a result, many EFL learners hold that English pronunciation is difficult to master, and they always find it difficult to speak confidently and intelligibly. This study is action research aimed at improving EFL students’ pronunciation by using songs in a blended learning environment. Conducted in April to May 2017, the study involved 30 tenth graders of a private senior high school in Depok, West Java, Indonesia. The face-to-face instructions were conducted in the language laboratory of the school, while the online sessions were conducted employing Edmodo as the learning management system (LMS). Learning activities were focused on using songs to improve the consonants, vowels, diphthongs, silent sounds, consonant clusters, stress and linking that were identified to be problematic for the participants in the pre-test. Data were collected by administering tests and questionnaires. The results showed that using songs in a blended learning environment improved the participants’ English pronunciation skills. The average scores of the three tests administered before, during, and after the project implementation successively increased. The data obtained from the survey revealed that pronunciation instruction using songs was interesting to the participants, helped their pronunciation improvement, and increased their self-confidence in English speaking.